APPLICATION OF INTERNET OF THINGS AND GATED RECURRENT UNIT FOR TEMPORARY IMMERSION SYSTEM - Kayantho, Royadi; NUHA, HILAL H; Setyorini, Setyorini; Sailellah, Hassan; Santoso, Gatot; Abdalla, Abdi Talib (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 6 No 1 (2025): JITTER, Vol.6, No.1, April 2025, 2025)
Application of Internet of Things (IoT) and Gated Recurrent Unit (GRU) technology in the Temporary Immersion System (TIS) system which can be used for orchid cultivation. Orchids, as ornamental plants with high economic value and widely exported in Indonesia, experiencing challenges in production that are not in line with increasing market demand. This limitation is caused by strict requirements for environmental conditions such as temperature, humidity, and Light intensity. TIS method combined with IoT and machine learning using GRU to predict temperature and humidity in the method TIS can monitor the temperature and humidity in the TIS incubator during orchid growth. Sensors will be used to collect environmental data, which is then processed to control incubator conditions in real-time. GRU machine learning, as an artificial neural network model used to predict environmental needs. Implementation of IoT and GRU The TIS method is expected to not only increase efficiency and quality orchid tissue culture, but also contribute to research in fields of agronomy and botany. This research includes problem identification, data collection, analysis requirements, tool creation, algorithm creation, tool testing, and manufacturing report. Evaluation of the accuracy of predictions of TIS incubator conditions using GRU will be done with metrics such as RMSE, MAE, MAPE, and R². Results of this research is expected to provide a new perspective on the use of advanced technology in agriculture and offers solutions to increase orchid production in Indonesia.